2004
DOI: 10.1128/iai.72.7.3932-3940.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Interleukin-4 (IL-4) in Pulmonary Paracoccidioidomycosis: Endogenous IL-4 Can Induce Protection or Exacerbation of Disease Depending on the Host Genetic Pattern

Abstract: Resistance to paracoccidioidomycosis, the most important endemic mycosis in Latin America, is thought to be primarily mediated by cellular immunity and the production of gamma interferon. To assess the role of interleukin-4 (IL-4), a Th2 cytokine, pulmonary paracoccidioidomycosis in IL-4-depleted susceptible (B10.A) and intermediate (C57BL/6) mice was studied. Two different protocols were used to neutralize endogenous IL-4 in B10.A mice: 1 mg of anti-IL-4 monoclonal antibody (MAb)/week and 8 mg 1 day before in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
1
22
0
11
Order By: Relevance
“…In the chronic phase of the disease, susceptible animals presented a transitory secretion of IL-2, and IL-4, and in the pulmonary infection, IL-4, IL-5 and IL-10 were preferentially detected in lung cells' washings of susceptible animals [62]. In addition, Arruda et al [131], demonstrated a dual role for IL-4 in pulmonary paracoccidioidomycosis, as endogenous IL-4 could induce protection or exacerbation of the disease depending on the host genetic pattern. Other study showed that IL-12 protects mice against disseminated infection caused by P. brasiliensis, but enhances pulmonary inflammation [132].…”
Section: Production Of Cytokinesmentioning
confidence: 99%
“…In the chronic phase of the disease, susceptible animals presented a transitory secretion of IL-2, and IL-4, and in the pulmonary infection, IL-4, IL-5 and IL-10 were preferentially detected in lung cells' washings of susceptible animals [62]. In addition, Arruda et al [131], demonstrated a dual role for IL-4 in pulmonary paracoccidioidomycosis, as endogenous IL-4 could induce protection or exacerbation of the disease depending on the host genetic pattern. Other study showed that IL-12 protects mice against disseminated infection caused by P. brasiliensis, but enhances pulmonary inflammation [132].…”
Section: Production Of Cytokinesmentioning
confidence: 99%
“…Importantly, the early administration of IL-12 does not reverse the susceptibility of B10.A mice but induces an excessive pulmonary inflammation (30). IL-4 depletion, instead of abolishing the susceptibility of B10.A mice, induces a more severe disease (31). Moreover, early in infection, higher levels of IFN-␥ were found in the lungs of B10.A but not A/J mice (32).…”
mentioning
confidence: 94%
“…Indeed, IL-4 is related with susceptibility and deficient formation of granulomas in P. brasiliensis-infected mice. 41,42 Altogether, these findings suggest that the expression of ICAM-1 in the lungs of mice infected with P. brasiliensis contributes not only to the recruitment and adhesion of circulating T cells but also to the formation and organization of granulomas and with the adequate balance of cytokine production. Together these events orchestrate the generation of effector immune responses and the host defenses responsible for preventing the fungus to escape and disseminate.…”
Section: Discussionmentioning
confidence: 78%